ארון הספרים ושפת החסד ביצירת אנטון שמאס - גינזבורג שי (מכאן, 2014)
In this essay, I read Anton Shammas’s novel Arabesques and its reception through the question of translation, which is simultaneously the question of origin and source. I suggest that this question informs the trope of the bookcase, one of the key tropes in the novel and its conceptual focus. Thus, in the first part of this essay, I examine Shammas’s bookcase from the perspective of an origin, whereas in the second part, I examine it from the perspective of translation. Yet, the trope of the bookcase pertains not only to the plot of Shammas’s novel, but also to the Israeli bookcase in general and to Shammas’s place as an author as well as a translator in it. The third section explores this latter matter. The final section of the essay ties together these divergent threads through a short reading of Walter Benjamin’s essay “The Task of the Translator,” which is one of Shammas’s own sources of inspiration.